Vhs2 is a novel regulator of septin dynamics in budding yeast - Cassani, Corinne (Landes Bioscience, 2014)
In budding yeast, septins are assembled into structures that undergo dramatic changes during the cell cycle. The molecular mechanisms that drive these remodelings are not fully uncovered. In this study, we describe a characterization of Vhs2, a nonessential protein that revealed to be a new player in septin dynamics. In particular, we report that Vhs2 is important to maintain the stability of the double septin ring structure until telophase. In addition, we show that Vhs2 undergoes multiple phosphorylations during the cell cycle, being phosphorylated during S phase until nuclear division and dephosphorylated just before cell division. Importantly we report that cyclin-dependent protein kinase Cdk1 and protein phosphatase Cdc14 control these Vhs2 post-translational modifications. These results reveal that Vhs2 is a novel Cdc14 substrate that is involved in the control of septin organization.